Prevalence of Parkinson's Disease in 22q11.2 Deletion Syndrome: A Multicenter Study - Emma N.M.M. von Scheibler; Ann Swillen; REPETTO LISBOA, MARIA GABRIELA; Nikolai Gil D. Reyes; Anthony E. Lang; Connie Marras; Mark L. Kuijf; Rob P.W. Rouhl; Agnies M. van Eeghen; Carlos Juri; Annick Vogels; Thérèse A.M.J. van Amelsvoort; et al. (Wiley, 2025)
Background deletion syndrome (22q11.2DS) has been associated with increased risk of early‐onset Parkinson's disease (PD).ObjectiveTo determine the prevalence and predictors of PD in a large international 22q11.2DS sample.MethodsThe sample comprised 856 adults (median age 28 (range 16–76) years; 53.0% female). PD was defined as clinical diagnosis by a neurologist (including bradykinesia, rest tremor and/or rigidity). Age‐specific risk and predictors of PD were analyzed using Kaplan–Meier curve and Cox regression.ResultsPD was present in 1.8% (95% CI: 0.9–2.6%) of the sample, 3.4% (95% CI: 2.2–4.6%) when including uncertain PD (clinical diagnosis or suspicion, but not meeting all criteria), and 14.0% (95% CI: 6.9–21.0%) of those aged ≥50 years. Median age at motor onset was 45 (range 20–66) years. None of the factors considered were associated with PD.ConclusionsGiven high PD prevalence and young onset, we propose periodic motor evaluations from age 40 years in 22q11.2DS